Advancing environmental monitoring across the water continuum combining biomarker analysis in multiple sentinel species: A case study in the Seine-Normandie Basin (France) - Sylvain Slaby; Alain Geffard; Cédric Fisson; Matthieu Bonnevalle-Normand; Anne-Sophie Allonier-Fernandes; Rachid Amara; Anne Bado-Nilles; Isabelle Bonnard; Marc Bonnard; Mayélé Burlion-Giorgi; Amélie Cant; Audrey Catteau; et al. (Journal of Environmental Management, 2024)

The past, present and future of genomic scans for selection - Jeffrey D. Jensen; Matthieu Foll; Louis Bernatchez (Molecular Ecology, 2016)

Inferring the age of a fixed beneficial allele - Louise Ormond; Matthieu Foll; Gregory B. Ewing; Susanne P. Pfeifer; Jeffrey D. Jensen (Molecular Ecology, 2016)
Estimating the age and strength of beneficial alleles is central to understanding how adaptation proceeds in response to changing environmental conditions. Several haplotype‐based estimators exist for inferring the age of segregating beneficial mutations. Here, we develop an approximate Bayesian‐based approach that rather estimates these parameters for fixed beneficial mutations in single populations. We integrate a range of existing diversity, site frequency spectrum, haplotype‐ and linkage disequilibrium‐based summary statistics. We show that for strong selective sweeps on de novo mutations the method can estimate allele age and selection strength even in nonequilibrium demographic scenarios. We extend our approach to models of selection on standing variation, and co‐infer the frequency at which selection began to act upon the mutation. Finally, we apply our method to estimate the age and selection strength of a previously identified mutation underpinning cryptic colour adaptation in a wild deer mouse population, and compare our findings with previously published estimates as well as with geological data pertaining to the presumed shift in selective pressure.

Enhanced AFLP genome scans detect local adaptation in high‐altitude populations of a small rodent ( Microtus arvalis ) - MARTIN C. FISCHER; MATTHIEU FOLL; LAURENT EXCOFFIER; GERALD HECKEL (Molecular Ecology, 2011)
Adaptation to adverse environmental conditions such as high altitude requires physiological and/or morphological changes. Genome scans provide a means to identify the genetic basis of such adaptations without previous knowledge about the particular genetic variants or traits under selection. In this study, we scanned 3027 amplified fragment length polymorphisms (AFLP) in four populations of the common vole Microtus arvalis for loci associated with local adaptation and high altitude. We investigated voles from two populations at high elevation (∼2000 m a.s.l.) representing the upper limit of the altitudinal distribution of the species and two geographically close low‐altitude populations ( F ST outlier approach specifically developed for AFLP markers, which considers the intensity of AFLP bands instead of mere presence/absence and allows to derive population‐based estimates of allele frequencies and F IS values. Computer simulations showed that this approach increases the statistical power of the detection of AFLP markers under selection almost to the power of single nucleotide polymorphism (SNP) data without compromising specificity. Our enhanced genome scan resulted in 20 prime candidate markers for positive selection, which show mostly extremely high allele frequency differences between the low‐ and high‐altitude populations. The comparison of global‐ and pairwise‐enhanced genome scans demonstrated further that very strong selective signatures may also be associated with single populations suggesting the importance of local adaptation in alpine populations of common voles.

Estimating population structure from AFLP amplification intensity - MATTHIEU FOLL; MARTIN C. FISCHER; GERALD HECKEL; LAURENT EXCOFFIER (Molecular Ecology, 2010)
In the last decade, amplified fragment length polymorphisms (AFLPs) have become one of the most widely used molecular markers to study the genetic structure of natural populations. Most of the statistical methods available to study the genetic structure of populations using AFLPs consider these markers as dominant and are thus unable to distinguish between individuals being heterozygous or homozygous for the dominant allele. Some attempts have been made to treat AFLPs as codominant markers by using AFLP band intensities to infer the most likely genotype of each individual. These two approaches have some drawbacks, the former discarding potentially valuable information and the latter being sometimes unable to correctly assign genotypes to individuals. In this study, we propose an alternative likelihood‐based approach, which does not attempt at inferring the genotype of each individual, but rather incorporate the uncertainty about genotypes into a Bayesian framework leading to the estimation of population‐specific F IS and F ST coefficients. We show with simulations that the accuracy of our method is much higher than one using AFLP as dominant markers and is generally close to what would be obtained by using the same number of Single‐Nucleotide Polymorphism (SNP) markers. The method is applied to a data set of four populations of the common vole ( Microtus arvalis ) from Grisons in Switzerland, for which we obtained 562 polymorphic AFLP markers. Our approach is very general and has the potential to make AFLP markers as useful as SNP data for nonmodel species.

In defence of model-based inference in phylogeography - MARK A. BEAUMONT; RASMUS NIELSEN; CHRISTIAN ROBERT; JODY HEY; OSCAR GAGGIOTTI; LACEY KNOWLES; ARNAUD ESTOUP; MAHESH PANCHAL; JUKKA CORANDER; MIKE HICKERSON; SCOTT A. SISSON; NELSON FAGUNDES; et al. (Molecular Ecology, 2010)